Diversification of Insurance Companies’ Products as Supporting Infrastructure Development Institutions in Indonesia - Mas Suroto, Wisudanto; Ramadhan, Bagaus Mohammad; Widiastuti, Tika; Andi, Irfan; Al Mustofa, Muhammad Ubaidillajh (CSID Journal of Infrastructure Development, 2019)
This paper analyses the product diversifications of insurance companies as supporting facilities for infrastructure development in Indonesia. Infrastructure development requires protection or guarantee and insurance as a medium for risk transfer hinders the implementation of infrastructure development both during the construction process and when the infrastructure is used. Product diversification carried out by insurance companies to support infrastructure development harms the company's financial performance. The more diversified business lines owned by insurance companies, the lower the company's financial performance. This will negatively impact the ability of insurance as a medium for risk transfer. On the other hand, huge ownership of market share and reinsurance will positively affect the financial performance of general insurance companies in Indonesia.